Exploring visitor perception and environmental element relationships in rock carving landscapes through random forest analysis - Wenxue Liu; Huan Li; Hao Sun; Qiaoyun Sun; Yishu Xia (PLoS ONE, 2025)
As a typical representative of cultural landscapes, the perceptual assessment of rock carvings encompasses not only the artistry of the carvings themselves but also the multi-dimensional impact of the surrounding environment on tourists. However, existing studies primarily focus on evaluating the artistic value of rock carvings while overlooking the influence of the environment on visitor experience. Taking Yeshan Spring and Autumn Garden as a case study, this research collected image data and visitor perception surveys to establish key perception indicators and employed the random forest method to analyze the importance of environmental factors and their association with visitor perception. The findings indicate that uniqueness and comfort are the key factors shaping visitor experiences, with rock carvings serving as the core anchors attracting visitors. Additionally, vegetation elements—particularly middle vegetation—demonstrated significant potential in influencing and enhancing visitor perception. This study preliminarily reveals the complex relationships between environmental elements and visitor perception and highlights the nonlinear contribution of the synergy among garden elements to improving visitor experience. Following the “one garden, one policy” design principle, this study emphasizes the importance of tailoring conservation and development strategies based on the unique natural conditions, historical and cultural background, and social needs of each garden. It underscores the necessity of optimizing the synergy among garden elements as an effective approach to enhancing visitor perception. By integrating quantitative techniques, this research constructs a more comprehensive evaluation system, providing a valuable reference for cultural heritage preservation and ecological sustainability.